The determinants of regional fertility in the Philippines - Calma, Alexandra Beatrice H.; Ponciano, Mark Allen B. (2013)
Policies that address the issues of fertility reduction and population growth in the country are often characterized as lacking in consistency, as observed from the vantage point of different administrations. However, fertility rates and population growth in the country were found to exhibit a negative trend for the past years. This paper explores the correlation between economic factors that ate associated with the decreasing trend in the total fertility rates in the Philippines. Regional panel data on the economic variables (a) total fertility rates; (b) average household income (c) contraceptive use/ prevalence; (d) female labor force participation rate; and (e) life expectancy were obtained and analyzed. Multiple linear regression was used to determine the significant relationship among variables which predict the negative trend in total fertility as experienced by the country. The researchers found out that among the four variables regresses against the regional total fertility rates, three variables were found to be significant, namely: life expectancy, contraceptive use/ prevalence, and average household income with average household income being the most significant predictor of fertility behavior. However, it must be noted that having household preferences concerning the desired number of children does not immediately lead to reduced fertility. Policy makers should be studying the characteristics of the population in order to have a better basis for policies on fertility reduction and population growth -- Author's abstract.